A Novel Right Handed Circular Polarization Folded Reflectarray Antenna at 60 GHz - Mohd Fairus Mohd Yusoff; Ronan Sauleau; Zaharah Johari; Mohamad Kamal A. Rahim; Huda A. Majid (Institute of Advanced Engineering and Science, 2017)
A novel right-handed circular polarization (RHCP) folded reflectarray antenna with optimized parameters is presented at 60GHz. The RHCP folded reflectarray antenna is designed using left handed circularly polarized selective surface (LHCPSS) Pierrot unit cell. Through simulation, it is shown that the antenna operates well at 60GHz. The maximum antenna directivity is 19dB with a reflection coefficient below -15dB. The radiation patterns showed good responses with side lobes level below -10dB. In addition, the best axial ratio at 60GHz is achieved as 0.75dB.